Let's Symbiose and Be With. A cross-disciplinary research and expression of amor mundi through electrifying living networks - Anna Pasco Bolta; Jean Manca; Robin Bonné (Inmaterial, 2024)
The sand of the seafloor is filled with electricity. Although it has been like that for millions of years, only about a decade ago, a group of Danish researchers found out that a microscopic hair-like bacterium is responsible for it. These so-called cable bacteria make electrical wires to transport energy over their bodies – a formerly unknown form of life. This unique creature has made scientists excited, intrigued and … in love. The bacterium attracted a lot of interested minds to Denmark. The fascination for cable bacteria crosses all fields of knowledge, initiating the collaborative project between art and science and thus giving the opportunity for different audiences to feel connected to the subject, regardless of their profession or background. The result was an exciting collaboration between scientists Robin Bonné and Jean Manca, and artist Anna Pasco Bolta, to create an art performance where a cable bacterium was fished from the mud and a love letter was read through a cable bacterium. Through the joint cross-disciplinary love letters of artist and scientists, they express their shared amor mundi, love for life and the world, together with their concerns and critical questions related to the fragile connections between life and the world. The cross-fertilisation of this scientific and artistic research connects fundamental questions on biosphere and technosphere, life, love and technology, symbiosis through electrical networks in nature and in our connected digital world. The artwork travelled around Europe, Canada and Egypt, and included a performance in front of 1500 microbiologists.